2020
DOI: 10.1177/1591019920954603
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality for patients with COVID-19 and large vessel occlusion

Abstract: Background This study evaluates the mortality risk of patients with emergent large vessel occlusion (ELVO) and COVID-19 during the pandemic. Methods We performed a retrospective cohort study of two cohorts of consecutive patients with ELVO admitted to a quaternary hospital from March 1 to April 17, 2020. We abstracted data from electronic health records on baseline, biomarker profiles, key time points, quality measures and radiographic data. Results Of 179 patients admitted with ischemic stroke, 36 had ELVO. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…46,65,67,68,108,110,115 Characteristically, LVO may affect younger patients without known risk factors for stroke, it is associated with higher in-hospital mortality and may represent the initial manifestation leading to hospitalization during SARS-CoV-2 infection. 65,67,115,116 Hypercoagulable state, cardioembolism, or paradoxical embolism due to COVID-19 may be potential reasons for such a stroke presentation. Furthermore, unexpected IS locations, such as in the corpus callosum or a frequent involvement of posterior circulation, have been associated with COVID-19.…”
Section: Red Flags For Covid-19-associated Stroke Diagnosismentioning
confidence: 99%
“…46,65,67,68,108,110,115 Characteristically, LVO may affect younger patients without known risk factors for stroke, it is associated with higher in-hospital mortality and may represent the initial manifestation leading to hospitalization during SARS-CoV-2 infection. 65,67,115,116 Hypercoagulable state, cardioembolism, or paradoxical embolism due to COVID-19 may be potential reasons for such a stroke presentation. Furthermore, unexpected IS locations, such as in the corpus callosum or a frequent involvement of posterior circulation, have been associated with COVID-19.…”
Section: Red Flags For Covid-19-associated Stroke Diagnosismentioning
confidence: 99%
“…Altschul et al found that patients with COVID-19 and emergent large vessel occlusion had a higher risk of mortality during the pandemic vs patients without COVID-19 (OR 16.63 [95% CI, 2.47–112], p = 0.004) and mortality was higher if patients were older than 60 years of age and had pulmonary symptoms. 11 In-hospital mortality was also found to be higher in patients with large vessel occlusion who had COVID-19 vs those without COVID-19 (41.7% vs 11.8%, p = 0.025) by Escalard et al 29 Jain et al found higher mortality risk (OR = 6.02 [95% CI, 2.6–14.6], p < 0.001) in COVID-19 patients with neuroimaging findings, the vast majority of which were ischemic or hemorrhage stroke (92.5%). 15 Ntaios et al was the largest study (174 patients) to report on mortality in large vessel acute ischemic stroke from 16 countries and found patients with COVID-19 had a higher risk of death (OR = 4.3 [95% CI, 2.22–8.30]) compared to matched COVID-19 negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from multiple published studies supports an association between COVID-19 and longer hospital stay, higher complications rates, worse functional outcomes and higher in-hospital mortality rates in AIS/LVO patients—whether they underwent MT or not—when compared with those without the infection. 3 , 16 18 , 26 , 35 , 40 , 41 A comprehensive cross-sectional study of patients from a large New York-based health care system found that stroke patients with COVID-19 had over a 9-fold increase in mortality compared with those without the infection. 42 Interestingly, they identified a higher risk of unfavorable outcomes in COVID-19 patients with ischemic stroke independent of traditional stroke risk factors and surrogates of stroke severity, which they attributed to the respiratory impact of COVID-19 on an already compromised patient with stroke.…”
Section: Methodsmentioning
confidence: 99%